Klasifikasi Calon Nasabah Baru Menggunakan C.45 Sebagai Dasar Pemberian Pertanggungan Asuransi di PT Asuransi Central Asia Pematangsiantar - Syahfitri, Retno Ayu; Windarto, Agus Perdana; Okprana, Harly (Bulletin of Data Science, 2021)
The problem that often arises in insurance problems is the number of customers who are in arrears in paying premiums, therefore a system is needed that can classify which prospective customers are in the eligible group and which customers are in the unfit group in submitting as insurance customers. so that the insurance company can solve the problem early. In this study, an information system for the classification of acceptance of prospective insurance customers was built using the Classification Tree C4.5. Classification tree C4.5 is used to generate the rules needed for the smooth classification process of customers in paying premiums and is formed from the conversion result of the construction of a classification tree (classification tree). The C4.5 algorithm is considered an algorithm that is very helpful in classifying data because the characteristics of the classified data can be obtained clearly, both (decision tree) and in the form of rules or If - then rules, making it easier for users to extract information on the data in question